2023
DOI: 10.1002/ana.26605
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinesia and Its Progression Are Related to Interhemispheric Beta Coherence

Abstract: Objective Bradykinesia is the major cardinal motor sign of Parkinson disease (PD), but its neural underpinnings are unclear. The goal of this study was to examine whether changes in bradykinesia following long‐term subthalamic nucleus (STN) deep brain stimulation (DBS) are linked to local STN beta (13–30 Hz) dynamics or a wider bilateral network dysfunction. Methods Twenty‐one individuals with PD implanted with sensing neurostimulators (Activa® PC + S, Medtronic, PLC) in the STN participated in a longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Accordingly, recorded activity in the STN and other components of the cortex -basal ganglia network may not reflect the typical Parkinsonian state. However, STN-LFP recordings months and years after implantation have repeatedly revealed similar profiles of activity to seen in the immediate post-operative state 46,[80][81][82][83] . Second, only a preliminary clinical review of stimulation parameters could be conducted to determine those used in the ON STN-DBS recordings.…”
Section: Limitationsmentioning
confidence: 75%
“…Accordingly, recorded activity in the STN and other components of the cortex -basal ganglia network may not reflect the typical Parkinsonian state. However, STN-LFP recordings months and years after implantation have repeatedly revealed similar profiles of activity to seen in the immediate post-operative state 46,[80][81][82][83] . Second, only a preliminary clinical review of stimulation parameters could be conducted to determine those used in the ON STN-DBS recordings.…”
Section: Limitationsmentioning
confidence: 75%
“…For instance, inter-hemispheric coupling in the beta range, but not power spectrum or burst dynamics, seems to correlate with progressive worsening in bradykinesia over time. 29 , 58 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Recently, one study revealed that the degree of STN–STN synchronization in the beta range (13–30 Hz) is associated with worse bradykinesia but not with tremor or rigidity. 29 …”
Section: Introductionmentioning
confidence: 99%
“…Aberrant beta band activity is robust over time [ 33 , 34 ]. Recently, there has been an interest into the effect of the state of dopamine and movement on the long-range beta functional connections between the basal ganglia and lower motor neurons, utilizing both STN LFP and electromyogram recordings [ 35 ].…”
Section: Brain Oscillation Fingerprints Of Parkinson's Diseasementioning
confidence: 99%